'How do I know what I think till I see what I say?' An aphorism and its implications for creative theorizing. Issue 1 (2nd January 2020) - Swedberg, Richard
ABSTRACT: The following aphorism is used as the point of departure for the discussion in this article: ' How do I know what I think till I see what I say ?' Its literal meaning is that it is through the very act of speaking that you get to know what you think; but the aphorism also has a suggestive quality to it. As a consequence, many artists and thinkers have referred to the aphorism and sometimes also elaborated on it. That the message of the aphorism is relevant for social science as well can be exemplified by the important interest that Robert K. Merton has shown for it, primarily to probe the process of creativity in science. Following up on Merton's ideas, but also taking them in a somewhat different direction, I argue that the aphorism may be of help when you try to theorize in a creative way in social science. Examples of this are provided.